Risk Factors for Low Back Pain among Educational Staff: A Cross-sectional Study at a Single University - Sari, Wahyuningsih Ratna; Jusuf, Herlina; Ahmad, Jusna; Kasim, Vivien Novarina A; Pateda, Sri Manovita (Jambura Medical and Health Science Journal, 2025)
Introduction: The work environment can pose risks of accidents or health issues for individuals or groups. Office jobs typically involve light tasks performed while seated at a desk in a well-equipped and comfortable workspace. However, such a work environment can create its own problems for workers, one of which is low back pain (LBP). This study aims to analyze the relationship between risk factors for low back pain among educational staff at Universitas Negeri Gorontalo.Methods: This study employed a cross-sectional design. The sample consisted of 186 educational staff at Universitas Negeri Gorontalo, selected using cluster random sampling technique. Data were collected through questionnaires and Rapid Upper Limb Assessment (RULA) observation sheets to assess age, work experience, smoking habits, stress, and work posture. Data analysis used chi-square test to examine the relationships between variables and logistic regression to identify the most influential variables.Results: The statistical analysis showed a significant relationship between LBP and age (p = 0.001) and work posture (p 0.001). Other factors such as gender, work experience, smoking habits, and stress did not show a significant relationship with LBP. Age had the greatest influence on LBP (Exp (B) = 0.427).Conclusion: Age and work posture are factors associated with the occurrence of LBP. Improving sitting posture while working and taking regular breaks to stretch are necessary to reduce the risk of LBP. An appropriate prevention strategy is crucial to protect workers from LBP, which can also lead to increased productivity.                                      Keywords: Age, educator professional, low back pain, work posture